PENDAPATAN DAN KESEJAHTERAAN PETERNAK KAMBING PE ANGGOTA DAN NON ANGGOTA KELOMPOK TANI DI DESA SUNGAI LANGKA KECAMATAN GEDUNG TATAAN KABUPATEN PESAWARAN - Hani Fitria Anggraini; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Lampung University, 2015)
This study aims to determine : 1) The factors affecting the farmer’s decision become farmers group members, 2) The income of members and non-members of goat farmers group, 3) The welfare level of members and non-members of goat farmers group. This study was conducted in Sungai Langka Village, Gedung Tataan Sub-district, Pesawaran Regency used by survey method. Respondents were 18 farmers group members and 45 farmers group non-members. Data collection was carried out in Juli-August 2014. The data analysis methods were done by qualitative descriptive and quantitative were used by Logit models, income of tabulation, and welfare analysis based on BPS’s criteria (2012). The results showed that 1) The income and sell price of goat farmers gave possitive effect against of the farmer’s decision become farmers group members, but their experiences gave negative effect, 2) There was differences of the farmer’s average income of goat farming. The income of farmers group members was higher than farmers group non-members, 3) The farmers group members and non-members classified as rich household. Key words : farmers group, income, PE’s goat, welfare